Inventing the new concept of 'learning' for the era of the 100-year life in Japan : creating society comprising countless 'small societies' organized through 'learning' /: creating society comprising countless 'small societies' organized through 'learning'. (2020) - Makino, Atsushi, 1960-
No abstract available